Which identity is the result of using the pythagorean theorem to show that a triangle with side lengths x^2 - 1, 2x, and x^2 + 1 is a right triangle?
A. (x^2 - 1)^2 + (2x)^2 = -(x^2 + 1)^2
B. -(x^2 -1)^2 + (2x)^2 = (x^2 +1)^2
C. (x^2-1)^2 + (2x)^2 = (x^2 +1)^2
D. (x^2 - 1)^2 - (2x)^2 = (x^2 + 1)^2

Respuesta :

9514 1404 393

Answer:

  C.  (x^2-1)^2 + (2x)^2 = (x^2 +1)^2

Step-by-step explanation:

Inexplicably, three of the four answer choices have minus signs in them. Those are all incorrect. The appropriate choice is ...

  C. (x^2-1)^2 + (2x)^2 = (x^2 +1)^2

__

Expanded, this is ...

  x^4 -2x^2 +1 +4x^2 = x^4 +2x^2 +1 . . . . the desired identity

Answer:

C.  (x^2-1)^2 + (2x)^2 = (x^2 +1)^2

Step-by-step explanation: